3PC-025 Galenic cannabis preparation and dispensation: an urban, alpine and rural district photography. (2nd March 2018) - Ceravolo, G; Strobino, S; Lecis, M; Viglione, E; Martinengo, S; Rosa, A
Abstract : Background: Cannabis-based herbal medicinal products are included in DPR 309/90. The Piedmont Region with DG. R. 24–2920, has decreed the prescribability of preparations based on cannabis sativa for approved indications, and the supply to the NHS is guaranteed by hospital pharmacies. Purpose: Study purposes are to collect and analyse prescriptions' typologies about regional NHS to make an efficient internal organisation to face the increasing preparations requests and collaborate with doctors to assure patients of an appropriate therapy. Material and methods: Hospital pharmacy has set preparations from June 2016 until today. Patients were classified by sex, age, drug, dose, cannabinoid and prescriber. An operational procedure for managing patient-sensitive data, raw material procurement, patient discharge on an internal database and patient management has been standardised. Any movement of the substances must be recorded in the drug register and the relevant documentation must be kept 2 years after the last transcription. Results: From June 2016 to June/2017, 256 preparations were formulated (12 080 doses). The currently undergoing patients are 61, 11% of whom take FM2 (available from January 2017), mainly as decoction, while 89% use bedrocan or bediol, with mean doses of 50 to 100 mg/twice daily. To speed up the set-up, plastic zipped food bags were used, which ensure product conservation, preserving it from moisture and heat. Expenditure for the purchase of raw materials in the second half of 2016 was €36114, and in the first half of 2017 €39 936. Conclusion: The major problems faced by the pharmacy in this first year of experience were the timing/amount of raw material supply from abroad, both for direct importation and through intermediate distributors. It has been necessary to optimise galenical setting times to cope with an increasing number of doses to be prepared. After this first year, we understand that in this hospital, because of the considerable amount of cannabis-related work, it will be necessary that a responsible pharmacist is assigned entirely to this whole sector (that means purchase of raw material, preparation, dispensation, registration). The pharmacist could collaborate with prescribers to detect a variability of doses, with the common aim of therapy standardisation and define a maximum allowable daily dose. Reference and/or Acknowledgements: 1. DGR-15/02/2016, n. 24–2920; Article 5, Law-94/98. No conflict of interest